Evaluation of Preoperative Nutritional Status of Patients with Gastrointestinal Cancer Using Different Nutritional Screening Tests - Sahin Kaya, Aysel; Pekcan, Gülden (Progress in Nutrition, 2021)
Background & Aims: To determine the nutritional status of gastrointestinal cancer patients with two different nutritional screening tools and compare the tools.Methods: This study was held in 110 patients (female; 41.8% male: 58.2%), aged 19-65 years, admitted to hospital, diagnosed with gastrointestinal system cancer (not operated). The objective was to determine the nutritional status of the patients with nutrition screening tools (Subjective Global Assessment-SGA, Nutritional Risk Screening-NRS 2002), compare the tools, and describe the malnutrition status of patients. Socio-demographic characteristics, anthropometric measurements, biochemical parameters and 24- hour dietary recalls, frequency of foods consumed were determined.Results: Out of total, 54.7% of males and 56.5% of females had normal Body Mass Index-BMI. Using SGA, 49.1% of the patients had serious, 41.8% had moderate degree of malnutrition. According to NRS-2002, percentages of severely, moderately and mildly undernourished patients were 54.6%, 33.6% and 11.8%, respectively. The percentage of patients meeting the recommended Daily allowances was 47.2% and 58.1%, respectively for males and females. According to NRS and SGA tools, statistically significant differences with current weight, ideal body weight, usual body weight, percentage of weight loss, body mass index (BMI), mid-upper arm circumference (MUAC), triceps skinfold thickness (TST), mid-upper arm muscle area, mid-upper arm muscle circumference and mid-upper arm fat area (p